Investigation on Development of Zein Antimicrobial Edible Film and Essential Oil of Zataria multiflora Boiss. on Sallmonella enteritidis, Listeria monocytogenes, Escherichia coli and Staphylococcus aureus - Ghasemi, Sara; Haji Seyed Javadi, Nasrin; Moradi, Mehran; Oromiehie, Abdolrasoul; Khosravi-Darani, Kianoush (Asian Journal of Chemistry, 2012)
Zataria multiflora Boiss' essential oil is a natural product that would be able to effect on food-borne bacteria. In this research ethanol based antimicrobial zein edible films containing added 0.00, 0.50, 1.00, 1.50, 2.00 % (w/v) Zataria multiflora and glycerol as a plasticizer were created. The films were effective against Salmonella enteritidis, Listeria monocytogenes, Escherichia coli 0157: H7 and Staphylococcus aureus.